Pengaruh Implementasi Akuntansi Berbasis Akrual, Sistem Pengendalian Intern dan Teknologi Informasi terhadap Kualitas Laporan Keuangan: Studi pada Pemerintahan Daerah Padang Pariaman - Sarma, Gimeilia; Fitra, Halkadri; Pebriyani, Dewi (Jurnal Nuansa Karya Akuntansi, 2023)
This study aims to see 1) The application of accrual-based accounting has an effect on the quality of financial reports in the Padang Pariaman Padang Pariaman Regional Government, 2) Technology and information have a significant influence on the quality of financial reports in the Padang Pariaman Padang Pariaman Regional Government. 3) The internal control system affects the quality of financial reports in the Padang Pariaman Regional Government. Padang Pariaman. 4) The application of accrual-based accounting, internal control systems and information technology have a significant influence on the quality of financial reports in the Padang Pariaman Regional Government. This study utilizes a quantitative design because this study is presented statistically. The population used in this research is 44 Regional Apparatus Work Units in the financial sector throughout Padang Pariaman Regency consisting of 427 employees based on data from the Personnel Service, Padang Pariaman Regency Education and Training Office in 2019. This research was carried out by distributing 207 questionnaires which will be distributed directly to the public. Regional Apparatus Work Unit in the financial section of Padang Pariaman Regency. Analysis of the data used in this study is using multiple regression analysis. Based on the results of the study, it was found that 1) The implementation of accrual-based accounting had a significant effect on the quality of the financial statements of the Padang Pariaman Regency Government. 2) The internal control system has a significant effect on the quality of the financial reports of the Padang Pariaman Regency Government. 3) The use of information technology has a significant effect on the quality of the financial statements of the Regional Government of Padang Pariaman Regency.